When your gay or lesbian child marries : a guide for parents - Merrill, Deborah M., 1962- (Rowman & Littlefield, 2016)
As more and more same-sex couples marry, their parents may need to learn new strategies for continuing healthy relationships with their children and their partners. This book offers a guide to understanding same-sex marriage and, through firsthand accounts, how natal family relationships change, yet can be loving and supportive.